Isu-Isu dalam Kaitan Pendidikan Perspektif Global Berwawasan ke SD-an - Nurcahyanti, Mei; Fitriana, Novita; Risdalina, Risdalina; Zahyuni, Violita (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2025)
Global education is becoming increasingly relevant in facing the challenges of the 21st century, including in the context of learning in elementary schools (SD). However, its implementation still faces various obstacles at the elementary education unit level. This article discusses five main issues that hinder the integration of global education in elementary schools, namely: (1) lack of teacher understanding of the concept and urgency of global education, (2) limited learning resources that support globally-oriented teaching, (3) dominance of local curricula that have minimal relevance to international issues, (4) difficulty in simplifying global issues to suit the characteristics of elementary school-age students, and (5) minimal training and policy support to strengthen teacher capacity. Through a literature review approach and reflective analysis of educational practices in Indonesia, this article highlights the importance of policy reform, improving teacher competence, and providing contextual learning resources so that global education can be implemented early on. It is hoped that this article will be an initial contribution to strengthening global education that is in line with the characteristics of elementary education in Indonesia.